Experiment for time-domain analysis using MATLAB app designer (II) - Mai, Tuan Minh (Nanyang Technological University, 2024)
This project leverages the Matlab APP Designer to provide a hands-on exploration of Signal and System theory, focusing specifically on the time-domain analysis critical to electrical engineering. Matlab, developed by MathWorks, appeared in the late 1970s to help engineers understand numerical computation, visualization, and programming.